Vaginal bacterial load in the second trimester is associated with early preterm birth recurrence: a nested case–control study. (19th July 2021) - Goodfellow, L; Verwijs, MC; Care, A; Sharp, A; Ivandic, J; Poljak, B; Roberts, D; Bronowski, C; Gill, AC; Darby, AC; Alfirevic, A; Muller‐Myhsok, B; et al.
Abstract : Objective: To assess the association between vaginal microbiome (VMB) composition and recurrent early spontaneous preterm birth (sPTB)/preterm prelabour rupture of membranes (PPROM). Design: Nested case–control study. Setting: UK tertiary referral hospital. Sample: High‐risk women with previous sPTB/PPROM <34 +0 weeks' gestation who had a recurrence ( n = 22) or delivered at ≥37 +0 weeks without PPROM ( n = 87). Methods: Vaginal swabs collected between 15 and 22 weeks' gestation were analysed by 16S rRNA gene sequencing and 16S quantitative PCR. Main outcome measure: Recurrent early sPTB/PPROM. Results: Of the 109 high‐risk women, 28 had anaerobic vaginal dysbiosis, with the remainder dominated by lactobacilli ( Lactobacillus iners 36/109, Lactobacillus crispatus 23/109, or other 22/109). VMB type and diversity were not associated with recurrence. Women with a recurrence, compared to those without, had a higher median vaginal bacterial load (8.64 versus 7.89 log10 cells/mcl, adjusted odds ratio [aOR] 1.90, 95% CI 1.01–3.56, P = 0.047) and estimated Lactobacillus concentration (8.59 versus 7.48 log10 cells/mcl, aOR 2.35, (95% CI 1.20–4.61, P = 0.013). A higher recurrence risk was associated with higher median bacterial loads for each VMB type after stratification, although statistical significance was reached only for L. iners domination (aOR 3.44, 95% CI 1.06–11.15, P = 0.040). Women with anaerobic dysbiosis or L. iners domination had a higher median vaginal bacterial load than women with a VMB dominated by L. crispatus or other lactobacilli (8.54, 7.96, 7.63, and 7.53 log10 cells/mcl, respectively). Conclusions: Vaginal bacterial load is associated with early sPTB/PPROM recurrence. Domination by lactobacilli other than L. iners may protect women from developing high bacterial loads. Future PTB studies should quantify vaginal bacteria and yeasts. Tweetable abstract: Increased vaginal bacterial load in the second trimester may be associated with recurrent early spontaneous preterm birth. Tweetable abstract: Increased vaginal bacterial load in the second trimester may be associated with recurrent early spontaneous preterm birth.